La traduction et les limites de la fidélité - Bogacki, Krzysztof (Studia Romanica Posnaniensia, 2007)
This article is devoted to the problem of divergence occurring among different versions of translation of the same text. On the basis of investigated translations by Polish oustanding poets of La Fontaine’s Fables into Polish the author offers a classification of divergences found. This classification takes into consideration both the semantic and formal factors.